Technical Analysis of Euphorbia caducifolia Haines Latex of South-East Asian Origin - Part I. Issue 3 (August 2013) - Bhattacharyya, Sanjay K.; Kar, Saptarshi; Chakraborty, Sugata; Dasgupta, Saikat; Mukhopadhyay, Rabindra; Bandyopadhyay, Abhijit
Identification and characterization of the latex from Euphorbia caducifolia Haines has been thoroughly described in this article. The average total solid content (TSC) of the latex was 27% and pH was found to vary between 6 to 7. About 70% by weight of the whole coagulum (Cog) was found soluble in toluene; rest was insoluble. Toluene soluble portion (TE) was mainly composed of terpenes and terpenoids of three different molecular weights; the lowest molecular weight fraction being the dominant (82%) one. Presence of about 8% natural rubber (NR, a polyterpene), mostly of cis configuration, was also identified from the composition analysis of that portion. Due to dominant low molecular weight mass, it was tackier as compared to Cog portion when manually felt. Thermal characterization showed a low temperature melting behavior (starting at 70°C for Cog and at 104°C for TE), ideal for a tackifier resin. Both Cog and TE portions were found to exhibit high thermal decomposition temperature ensuring high process safety. The ash was rich in magnesium oxide and has a great potential to be used as the cure retarder in certain rubber compounds. Absence of any deleterious metals like copper, manganese etc. was also a great positive point towards its application standpoint.